Litigated democracy judicial disenfranchisement of voters through annulment of elections (Philippine Law Journal, 2021)
The increasing number of election contests in the country, including no less than that of the vice-presidency, accentuates the role of the courts, the electoral tribunals, and the Commission on Elections (COMELEC) in ascertaining the true sovereign will of the electorate when challenged with claims of fraud, terrorism, and other irregularities. While the law devises modes by which such contests may be lodged, the Supreme Court's recent pronouncements made it possible for other remedies so extreme such as that of annulment of elections to be availed of. This Note explores the history of this power granted upon electoral tribunals, the procedure by which it may be lodged, and the consequences of the grant of such remedy concomitant with the existing power of the COMELEC to declare failure of elections. In so doing, the analysis in this Note hopes to contribute to a more structured and nuanced discussion of this remedy in order to lay down the framework, the conditions, and the procedure before courts may be allowed to disenfranchise en masse the sovereign will of the electorate, the very essence of our democracy, if allowed at all.